The Eerdmans dictionary of early Judaism - Collins, John J.; Harlow, Daniel C. (William B. Eerdmans Publishing Company, 2010)
Essays. Early Judaism in modern scholarship / John J. Collins -- Jewish history from Alexander to Hadrian / Chris Seeman and Adam Kolman Marshak -- Judaism in the land of Israel / James C. VanderKam -- Judaism in the diaspora / Erich S. Gruen -- The Jewish scriptures : texts, versions, canons / Eugene Ulrich -- Early Jewish biblical interpretation / James L. Kugel -- Apocrypha and pseudepigrapha / Loren T. Stuckenbruck -- Dead Sea scrolls / Eibert Tigchelaar -- Early Jewish literature written in Greek / Katell Berthelot -- Archaeology, papyri, and inscriptions / Jürgen K. Zangenberg -- Jews among Greeks and Romans / Miriam Pucci Ben Zeev -- Early Judaism and early Christianity / Daniel C. Harlow -- Early Judaism and rabbinic Judaism / Lawrence H. Schiffman -- Dictionary entries A-Z